FROM OKINAWA TO JAVA: RECORDS OF RYUKYU KINGDOM LETTERSTO MAJAPAHIT: Dari Okinawa ke Jawa: Catatan Surat Kerajaan Ryukyu untuk Majapahit - Akbar Rizqi Dhea Habibi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This article examines the fifteenth-century diplomatic and trade relations between the Ryukyu Kingdom (Okinawa, Japan) and the Majapahit Kingdom (Java) on the basis of six letters recorded in the Rekidai Hōan. Dated between 1430 and 1442 CE, these documents provide concrete evidence of official Ryukyuan missions to Majapahit and allow a closer reconstruction of how inter-kingdom communication was conducted across maritime Asia. The letters indicate exchanges of high-value goods—such as brocade textiles, porcelain, and weapons—whose circulation functioned not only as economic transactions but also as markers of status and political recognition within a wider regional order. Although surviving references to Majapahit’s return gifts are limited, the repeated dispatch of missions suggests a sustained expectation of reciprocity and mutual acknowledgement, as well as an interest in opening or maintaining commercial channels. The study highlights Ryukyu’s strategic role as a maritime intermediary linking East and Southeast Asia, while also affirming Majapahit’s wide-ranging maritime diplomacy near the end of its golden era. Despite its relatively short duration, this contact illustrates the complex dynamics of precolonial inter-polity relations, shaped by negotiation of rank, commodity mobility, and seaborne networks across Asia.